2009
DOI: 10.1007/s10452-009-9231-1
|View full text |Cite
|
Sign up to set email alerts
|

No more lake balls (Aegagropila linnaei Kützing, Cladophorophyceae, Chlorophyta) in The Netherlands?

Abstract: Aegagropila linnaei, a freshwater green macroalga, had been abundant in several locations in The Netherlands before the 1960s. Both the 'lake ball' form of this alga and dense unattached mats floating over the sediment have been described from these locations. After 1967, this species has not been recorded anymore from The Netherlands. In 2007, several historical collection sites were surveyed for extant populations of A. linnaei. All habitats have changed drastically during the last 50 years and were affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 24 publications
0
17
0
4
Order By: Relevance
“…Detailed knowledge of the distribution of a species is important both for evolutionary studies and with respect to conservation. Several studies have reported declining or extinct populations of A. linnaei in connection with eutrophication (Pankow, 1985;Wakana et al, 2001Wakana et al, , 2005Wakana et al, , 2006Einarsson et al, 2004;Boedeker & Immers, 2009;Boedeker et al, 2010). In this study, a comprehensive overview of the distribution of A. linnaei is given, based on herbarium specimens, available literature data and recent field observations.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Detailed knowledge of the distribution of a species is important both for evolutionary studies and with respect to conservation. Several studies have reported declining or extinct populations of A. linnaei in connection with eutrophication (Pankow, 1985;Wakana et al, 2001Wakana et al, , 2005Wakana et al, , 2006Einarsson et al, 2004;Boedeker & Immers, 2009;Boedeker et al, 2010). In this study, a comprehensive overview of the distribution of A. linnaei is given, based on herbarium specimens, available literature data and recent field observations.…”
Section: Introductionmentioning
confidence: 93%
“…, 2001, 2005, 2006; Einarsson et al. , 2004; Boedeker & Immers, 2009; Boedeker et al , 2010). In this study, a comprehensive overview of the distribution of A. linnaei is given, based on herbarium specimens, available literature data and recent field observations.…”
Section: Introductionmentioning
confidence: 99%
“…An extremely rare freshwater alga, Aegagropila linnaei , is known for its beautiful spherical filamentous aggregations [ 4 ]. It has become popular in the souvenir and aquarium trades, and is depicted on postage stamps from Japan and Iceland [ 1 , 5 ]. This alga is an endangered or protected species in Japan, Iceland, United Kingdom, Germany, Sweden, and Russia, because of declining populations, and is included in national red lists and other conservation strategies [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has become popular in the souvenir and aquarium trades, and is depicted on postage stamps from Japan and Iceland [ 1 , 5 ]. This alga is an endangered or protected species in Japan, Iceland, United Kingdom, Germany, Sweden, and Russia, because of declining populations, and is included in national red lists and other conservation strategies [ 5 , 6 ]. Scientifically, however, the mechanism for forming spherical aggregations has been researched and discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation